(untitled) (Research, Society and Development, 2021)
The use of sodium hypochlorite (NaOCl) as irrigation solution in endodontics is widespread and accidents of apical extravasation may occur, being in most cases mild to moderate situations of simple management. However, in immunosuppressed patients, the reaction may be exacerbated, with significant systemic changes and potentially life-threatening. Even so, there is a lack of information about the management of these special cases, especially in oncopediatric cases. Therefore, the aim is to report a case of severe reaction post-accident with NaOCl in a 13-year-old adolescent undergoing chemotherapy, with significant edema, gingival necrosis, cutaneous rash, edema of the extremities, pleural effusion, and bronchopneumonia, with a 30-day evolution. It is understood that several factors, including anatomical, may predispose this situation, which can occur even with expert and experienced professionals, not necessarily associated with poor practice. The authors raise the importance of further studies to discuss the real need and indication of the use of NaOCl as an irrigating solution for these patients and suggest the adoption of extra safety measures to avoid the occurrence of similar situations.